Studi Kasus: Optimalisasi Regenerasi Kulit Pasca Prosdeur Estetik dengan Perawatan Kulit Dermo-kosmetik - Setiawan, Stanley; Darmawan, Hari; Putranto, Samuel S; Linata, Angela M; Salim, Stephanie; Nobel, Shelly (Universitas Kristen Maranatha, 2024)
The use of ecobiology-based dermocosmetics containing Antalgicine™ can expedite the optimization of skin regeneration post-aesthetic procedures. The aim of this case study assess the clinical benefit of Antalgicine™ post-aesthetic procedures. Six patients were recruited into this case study which utilizes subjective and objective measurements. Antalgicine™ was applied using a split-face study method. Subjective evaluation is graded by patients using a 1-5 Likert scale, along with objective evaluation, was performed by a blinded dermatologist. Results showed an objective reduction in post-aesthetic procedure on day 7, namely 40% for microneedling, 32% for fractional radiofrequency, and 29% for picosecond laser, as well as subjective reductions in every post-aesthetic procedure sensation, specifically pain, pruritus, tightness, and burning sensation at 67%, 75%, 67%, 33% for microneedling, 71%, 67%, 67%, 50% for fractional radiofrequency, and 67%, 75%, 78%, 60% for picosecond laser, respectively. As a conclusion, Antalgicine™ can reduce post-aesthetic procedure effects for optimizing skin regeneration.